Perlindungan Hukum dalam Perjanjian Sewa Guna Usaha Berbasis Asas Kebebasan Berkontrak - Syaiful Khoiri Harahap (CV Rewang Rencang, 2025)
Leasing is one of the solutions for society to acquire the goods they desire in order to improve their standard of living. A leasing agreement is an innominate contract, meaning that its formation is left to the parties involved to determine the clauses within the agreement. The research method used is based on normative legal research with a statutory approach and a conceptual approach. The research findings indicate that leasing agreements are implemented in the form of standard contracts following the